ANALISIS PENYEBAB BOTTLENECK PADA SUATU KOMPUTER MENGGUNAKAN APLIKASI BENCHMARKING CRYSTALDISKMARK DENGAN METODE SWOT (Universitas Sains dan Teknologi Komputer Semarang, 2022)
This research is a research that aims to find the right solution in the midst of the problem of affordable laptop or computer products where if we run a program there will be a bottleneck if there is a component that inhibits the function of the CPU (Central Processing Unit) working system. future problems because everyone definitely needs a fast but cheap device in order to boost the performance of a laptop or budget computer, so the effectiveness with time can increase sharply because of using the product, this study also compares a device that causes bottlenecks and a device that can become a problem a solution so that everyone can feel the benefits when this tool is installed on a laptop or computer system. This research is a Research and Development (R&D) research using the Benchmarking model and data collection is supported through Troubleshooting Computers and Laptops using the SWOT Method. The cause of the bottleneck they will face. With this application, we hope that the results of this study can help overcome the problems faced by some people who face their computers or laptops experiencing systems that are slow to respond to the wishes of computer or laptop users.